HUBUNGAN KERJA ANTARA KEPALA DAERAH DAN DEWAN PERWAKILAN RAKYAT DAERAH DALAM PEMBUATAN PERATURAN DAERAH DI KABUPATEN SINTANG - Cynthia Apriani E.42009034 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2022)
The writing of this undergraduate thesis is hoped to be considered to handle problems between the District Head and the House of Representative of Regency in the domain of the Local Government of Sintang Regency. This research is meant to describe the implementation of working relation between the District Head and the House of Representative of Sintang Regency in the making of Regional Regulation. This undergraduate thesis is put forward in accordance with problems that more dominant role od District Head (executive heavy) compared with the House of Representative of Regency whereas the pattern of relation that should be balanced (check and balance). The house of representative of Recency still less active when compared with the filling of drafting regional regulation. This research utilizes qualitative method in the kind of descriptive research. The data collection is done by utilizing technique of observation, interview, documentation. This research location is the Regional Government of Sintang and the Regional House of Representative Offices of Sintang Regency. The research subject is the Regent of Sintang, the speaker of Regional House of Representative, Regency Secretary of Sintang Government, the Secretary of Regional House of Representative of Sintang Regency,  and the Commision One of the Government of Sintang Regency. The devices of collecting data in this research are interview, observation and documentation. The result of this research is to see how the planning of the implementation of working relation between the executive and the legislative bodies which have equivalent position and partnership in drafting Regional Regulation of Sintang Regency in order not to be mutual domination in position. Keywords      : Head of Sintang Regency, Draft of Regional Regulations, Implementation of working Relation.